Analisis Geometri Jalan Angkut Tambang Pada Aktivitas Pertambangan Batubara di PT. Haswi Kencana Indah, Kabupaten Tebo, Provinsi Jambi. - Assidiqi, Afwan (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
The coal transportation process is carried out from the mining site to the stockpile as far as ± 40 km so that the coal haul road has an important role in supporting the productivity of coal transportation activities at PT Haswi Kencana Indah. The coal transportation production plan is 32,929.0833 tons / month, but the actual condition of coal transportation is 25,000 tons / month so that the production target is not achieved. The purpose of this research is to improve the geometry of the haul roads of PT Haswi Kencana Indah. The method used in this research is observation and data analysis with calculations. The road width conditions that do not meet the standards are the actual straight road widths for the D-E, F-G, I-J and K-L segments, while the curved road widths are the C-D, E-F and H-I segments. The improvements made were changes in the width of the straight road to 8.75 meters, at a bend of 15.706 m, making a cross slope of 35 cm, making a super elevation with a height difference between the right and left sides of the road by 21 cm to 97.6 cm and carrying out road maintenance so that coal productivity increases.